Age-related circadian rhythm and variability of large- and small-airway function in healthy non-smoking adults: Data from 7-day diurnal and nocturnal home monitoring using an electronic portable spirometer - Zhang, Xue; Zhang, Yingying; Zhou, Yan; Yin, Dongning; Lv, Chengjian; Lin, Jinwang; Bao, Wuping; Zhang, Min (Frontiers in Public Health, 2022)
Background: To investigate the possible influencing factors of the large- and small- airway function variation in healthy non-smoking adults. Methods: Healthy non-medical adults without smoking were enrolled in this prospective cohort study. Each participant performed the portable spirometer test relying only on the video teaching first. Then conventional spirometry and bronchodilation test were conducted with Jaeger spirometer, followed by 7-day diurnal and nocturnal home monitoring with portable spirometer. Results: A drop of both large- and small- airway function began at about 25 yrs of age, and a rapidly decline at about 50 yrs. The CV of FEV1 (r =0.47, P = 0.0082) and small airway function variables correlated with age (r ≥ 0.37, P < 0.05 for both MEFs and MEFs/FVC), especially for evening small airway function variables. The CV of large (4.666 ± 1.946, P = 0.002 for FEV1; 4.565 ± 2.478, P = 0.017 for FEV3) and small airway (10.38 ± 3.196, P = 0.031 for MEF50 and 11.21 ± 4.178, P = 0.023 for MMEF) was higher in 45-60 yrs subgroup, compared with 30-45 yrs and 18-30 yrs subgroup. Interpretation: Age was the main influencing factor of both central and peripheral airway function variability, especially for the small airway function during the evening term. The LLN of small-airway variables should vary depending on the age and circadian rhythm. People older than 45 yrs should pay more attention to monitoring small airway function in the evening, which is helpful for early clinical detection of population at high-risk for asthma.